1984
DOI: 10.1073/pnas.81.14.4606
|View full text |Cite
|
Sign up to set email alerts
|

Local structure involving histidine-12 in reduced S-sulfonated ribonuclease A detected by proton NMR spectroscopy under folding conditions.

Abstract: The CEH proton resonance of His-12 of reduced cysteine S-sulfonated bovine pancreatic ribonuclease A exhibits a nonlinear temperature dependence of the chemical shift in its 1H-NMR spectrum at an apparent pH of 3.0. At temperatures below ca. 35TC, the temperature dependence of the chemical shift of the His-12 CEH resonance is opposite in sign to those of His-48, His-105, and His-119. At temperatures above ca. 35TC, the temperature dependence of the chemical shift of the His-12 CEH resonance is similar to those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 55 publications
(86 reference statements)
1
16
0
Order By: Relevance
“…Experimental results from a combined sample of RNase A and the S-peptide, residues 1-20, demonstrated that resonance D belongs to the C'H of His-12 (see following section). The chemical shift of peak C is very similar to the chemical shift of C'H His-105 in disulfide-reduced and sulfonated RNase A (Swadesh et al, 1984). The C'H His resonances of sulfo-nated RNase A (8S032~-RNase A) were assigned by selective deuteriation procedures.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Experimental results from a combined sample of RNase A and the S-peptide, residues 1-20, demonstrated that resonance D belongs to the C'H of His-12 (see following section). The chemical shift of peak C is very similar to the chemical shift of C'H His-105 in disulfide-reduced and sulfonated RNase A (Swadesh et al, 1984). The C'H His resonances of sulfo-nated RNase A (8S032~-RNase A) were assigned by selective deuteriation procedures.…”
Section: Resultsmentioning
confidence: 82%
“…In order to examine the formation of structure in the refolding ensemble in greater detail, ID NMR spectra of the nonnative forms of RNase A were taken from 11 to 70 °C. This approach has been used by several investigators to study the formation of compact structures in chemically modified, nonfolding forms of RNase A (Rico et al, 1983(Rico et al, , 1986; Kim & Baldwin, 1984;Swadesh et al, 1984). The term nonnative RNase A refers to conformations found in both the refolding ensemble and the heat-denatured protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unfolded state ensembles of a number of proteins have been characterized by NMR and other spectroscopic methods. Depending on solution conditions, the unfolded states may show conformational preferences for native-like or non-native residual structure (Swadesh et al, 1984;Dill and Shortle, 1991;Neri et al, 1992;Sosnick and Trewhella, 1992;Shortle, 1993;Logan et al, 1994;Arcus et al, 1995;Buckler et al, 1995;Ittah and Haas, 1995;Dyson and Wright, 1998;Navon et al, 2001;Yao et al, 2001;Schwarzinger et al, 2002). But there are relatively few proteins whose folding transition states have been characterized in detail.…”
Section: Discussionmentioning
confidence: 99%
“…By monitoring the chemical shifts of the His C 1 H resonances, we identified the local structure in the vicinity of His 12 in reduced S-sulfonated RNase A (Swadesh et al, 1984) and in the disulfide-intact guanidine-denatured protein (Bierzynski & Baldwin, 1982). Predictions, based on hydrophobic interactions in the wild-type protein, have determined that the C-terminal region including residues 105-124 is the primary region of initial structure formation or CFIS (Matheson & Scheraga, 1978).…”
Section: Evidence Of Local Structure Involving a His Residuementioning
confidence: 99%